Prop up the Farming Community with E-Services: Web Based Services for Agriculture (International Journal of Engineering and Computer Science, 2016)
Agriculture is the backbone of many developing country economies. Agricultural development becomes same with worldwide development. Information of adequate quality is an essential stipulation for progress of all areas of agriculture and its allied areas with the quick development of Information and Communication Technologies (ICT), data and information could efficiently created, stored, analyzed and disseminated to support farming communities for improvement of agricultural productivity and sustainability. e-services is one of the best and foremost methodologies in ICT which can be achieved via the internet to share the information and knowledge from the bureaucrat community to farming community and it is also reaches the end-user in easy and simple way being it is a mobile based era.